ARE ALL WOMEN FEMINISTS? A CRITICAL VIEW ON LADY BIRD (2017) FILM - Putra, Gesang Manggala Nugraha; Kharisa, Trisnavia Elma (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2020)
In the study of film as media, there is a growing tendency on labelling films with female leads and female production crews as feminist films. This study aims to test such claim in the film Lady Bird (2017). To do so, the study employs Feminist Identity Development Model by Downing and Roush to look at the main lead of the film, along with analyses on the film’s narrative and cinematographic aspects. The study finds that the female lead fails to undergo all the five stages of Feminist Identity Development Model. The study further explores that her advancement through the stages is being held back by her dependence to her family and those around her. The study, then, suggests some further inquiries on the interrelatedness of age and feminism.